CONTEXTUAL INFLUENCES ON HEALTH AND WELL-BEING - Munoz, E (Innov Aging, 2018)
The environmental, social, and psychological contexts in which aging individuals are embedded may play an important role in limiting or promoting healthy aging. These contexts may also aid in better understanding health disparities in aging adults. Our objective is to bring together a collection of papers that advance theory on the role that a person’s context, across different levels of analysis, has on their health and well-being and that highlight relevance for diverse (e.g., rural aging, racial/ethnic minority) aging adults. These presentations will include a study by Harris and colleagues on geographical factors and regional differences in service resources available in rural communities for older adults. Munoz and colleagues will present results of a coordinated analysis of three studies of diverse midlife adults that evaluates the association between psychosocial neighborhood stress on cognitive function. Sardina and colleagues will present results on the effects of perceived neighborhoods and depressive symptoms on the consistency of objective and subjective pain measurements in a diverse sample of aging adults using data from the Healthy Aging in Neighborhoods of Diversity Across the Lifespan Study. Employing data from the Health and Retirement Study, Muruthi and colleagues will present results on the longitudinal effects of previous depressive symptoms and spousal support on current depressive symptoms among Hispanic aging adults. The discussion by Christine Mair will integrate these papers, discuss theoretical and methodological promises, and highlight challenges of research on the role of contextual embedding on emotional, physical, and cognitive health in diverse aging adults.